The Semiotics of the Commodity in the Marxian Concept of Value - Dantas, Marcos (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2020)
The Marxian concept of value is a cultural and hence a semiotic concept, rather than economic. Based on a scrutiny of Marx’s writings, this article proposes that Marx’s analysis of the commodity can and should also be interpreted as a semiotic treatise. This insight may also be relevant to contemporary Marxian investigations concerning labour and value in capitalism insofar as the notion of value of commodities is concerned. Whereas the literature on the crisis of value theories has focused primarily on the relationship between use value and exchange-value (and abstract labour), the present paper focuses on the aspect of the sign value of commodities in Marx’s theory and on how the notion of value represents of human labour.